Hubungan Tingkat Pengetahuan Ibu Hamil tentang COVID-19 dengan Kepatuhan Protokol Kesehatan pada Kehamilan - Rezqiqah Aulia Rahmat; Cakrawati Cakrawati; Sahalia Sahalia (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
The COVID-19 pandemic poses a major challenge to the health of pregnant women. The level of knowledge of pregnant women about COVID-19 is thought to be related to their compliance with health protocols. This study aims to determine the relationship between the level of knowledge of pregnant women about COVID-19 and their compliance with health protocols during pregnancy. The research method used a quantitative approach with a cross-sectional design. The study population consisted of pregnant women who underwent pregnancy check-ups at health care facilities, with the sample size determined through purposive sampling. The results showed that pregnant women with a high level of knowledge tended to be more compliant in following health protocols such as wearing masks, maintaining physical distance, and washing hands compared to pregnant women with low knowledge. In conclusion, there is a significant relationship between pregnant women's knowledge level about COVID-19 and their compliance with health protocols.